Biosynthesis of Silver Nanoparticles from Callistephus chinensis Flower Waste: Evaluation of Antibacterial, Anticancer, and Contaminated Water Remediation Applications - Kakodkar, Shruti; Dhawal, Pranjali; Kadam, Janvi; Khan, Rumanna; Shewale, Pradnya; Chaukekar, Tejaswi (Journal of Multidisciplinary Applied Natural Science, 2025)
The present study explored antibacterial and anticancer properties of silver nanoparticles (AgNPs) uniquely synthesized using aster (Callistephus chinensis) flower waste (AFW) via a microwave-assisted approach. The nanoparticles were also tested for their effectiveness in treating coliform-contaminated borewell water. The AFW extract was characterized using LC-HRMS and quantitatively analysis using TPC and TFC assays. Nanoparticle characterization was performed using UV-spectroscopy, FT-IR, SEM, EDX, TEM, SAED and XRD instruments. The AFW extract showed 1.6687 mg of gallic acid equivalent (GAE) and 9.71 mg quercetin equivalent TPC and TFC, respectively. The LC-HRMS profile also revealed the presence of various polyphenols followed by organic acids and alkaloids. The minimum inhibitory concentration required to inhibit 90% of bacterial growth (MIC90) was determined against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The cytotoxic activity of AgNPs was analyzed against cervical cancer cell line HeLa and normal human dermal fibroblast (HDF) cells. AgNPs exhibited a strong antibacterial activity, with MIC90 of 0.0625 mg/mL against E. coli and P. aeruginosa, and 0.125 mg/mL against S. aureus. Nanoparticle treatment did not alter the physicochemical parameters of borewell water beyond their permissible limits. According to MPN analysis, untreated borewell water contained 1600 coliforms/100 mL, which were eliminated following nanoparticle treatment (0 coliforms/100mL). AgNPs displayed anticancer activity against HeLa cell lines with an inhibitory concentration (IC50) of 0.21 mg/mL. The IC50 of AgNPs against normal HDF cells was 0.414 mg/mL — higher than that observed against HeLa cell lines and the bacterial MIC90, thus indicating selective cytotoxicity. To conclude, the study demonstrated the promising use of AFW in the green synthesis of AgNPs, which exhibited potent antibacterial and anticancer properties, along with low toxicity to HDF cell lines. These AgNPs also demonstrated promising applications in treating coliform-contaminated borewell water.